HACKER EDUCATION AND GAMIFICATION WITH RPG MAKER: ACTIVE METHODOLOGIES IN CRITICAL CYBERSECURITY TRAINING - Marcos Borges Paes, Tadeu; Ruan Silva Matos, Murilo (Journal of Interdisciplinary Debates, 2025)
Hacker education proposes a pedagogy based on curiosity, ethics, and experimentation. When associated with gamification, it gains a new space for creative expression, capable of transforming cybersecurity learning into an interactive and meaningful experience. This article analyzes the use of RPG Maker as a gamification tool and active methodology in Hacker Education, exploring its potential to develop investigative, ethical, and collaborative skills. From a theoretical-reflective approach, the fundamentals of challenge-based learning and the principles of game design are discussed as formative practices that stimulate critical thinking and the resolution of real-world problems in digital security contexts. The use of RPG Maker, in addition to bringing students closer to the logic of programming and the simulation of cyber incidents, enables the creation of educational narratives that awaken empathy, decision-making, and a sense of ethical responsibility. Thus, gamification emerges as a language and strategy for cognitive emancipation in the hacker training process.